Advance of wear resistance and durability of rolling bearings after ion nitriding - Каплун, П.В. (Problems of Tribology, 2016)
Kaplun P. V. Advance of wear resistance and durability of rolling bearings after ion nitriding.The experimental results of wear resistance and durability of the bearings in oil after the ion nitriding in different modes. The bearings are made of steel ShKh15 brand. Stress on bearing ball was equal to 150 N. The equations depending on the wear resistance and durability of the bearings on the technological parameters of ion nitriding process. Detected the optimal technology mode.